PERJUANGAN MENGHADAPI OBJEKTIFIKASI PEREMPUAN DALAM NOVEL ASTIRIN MBALELA KARYA SUPARTO BRATA - Sekar Wulan Murdaningrum; Ari Prasetiyo (Cross-border, 2023)
Astirin Mbalela's novel describes the life of a Javanese female character who struggles for her own existence as a subject because she experiences injustice caused by gender. This research aims to build awareness about the existence of objectification of women by deepening the discussion of existentialist feminism, especially in the context of Javanese culture which is considered foreign, so that it becomes a reference for the ethics of Javanese or non-Javanese society in society according to the idea of existentialist feminism. This study uses a qualitative descriptive research method with a feminist literary criticism approach. The results of this study show a form of objectification towards women and shows a form of resistance to Astirin's existence as a woman by using the Javanese cultural context, namely 'mbalela'. Astirin is a Javanese female character who can represent according to Simone de Beauvoir's existentialist feminist ideas. The representation of Astirin's character can be categorized into a form of struggle as a form of women's existence. In the context of Javanese culture which is represented through novels, this research provides a renewed discussion of the existence of Javanese women, especially in the context of feminism existensialism. With this research it is hoped that the phenomenon of objectification of women which in fact is detrimental to women can be reduced or even eliminated. Keywords: Astirin Mbalela, Suparto Brata, Existentialist Feminism, Simone de Beauvoir